2005
DOI: 10.1016/j.ccr.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a tumor suppressor role of HIF-2α

Abstract: The hypoxia-inducible transcription factors HIF-1alpha and HIF-2alpha are activated in hypoxic tumor regions. However, their role in tumorigenesis remains controversial, as tumor growth promoter and suppressor activities have been ascribed to HIF-1alpha, while the role of HIF-2alpha remains largely unknown. Here, we show that overexpression of HIF-2alpha in rat glioma tumors enhances angiogenesis but reduces growth of these tumors, in part by increasing tumor cell apoptosis. Moreover, siRNA knockdown of HIF-2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
133
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 63 publications
11
133
2
Order By: Relevance
“…Hypoxia-inducible factor-2a expression has not been studied in models of tumour carcinogenesis except in our work in the Barrett's metaplasia -dysplasia -adenocarcinoma sequence, where we showed that HIF-2a was expressed late in the sequence and was seen only in dysplasia and adenocarcinoma (Griffiths et al, 2007a). Recently, the overexpression of HIF-2a in rat gliomas was shown to have counteracting properties, in which angiogenesis was induced but reduced growth was also found due to increased tumour-cell apoptosis (Acker et al, 2005). Hypoxiainducible factor-2a expression has also been suggested to be critical in the carcinogenesis of renal cortical tumours (Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…Hypoxia-inducible factor-2a expression has not been studied in models of tumour carcinogenesis except in our work in the Barrett's metaplasia -dysplasia -adenocarcinoma sequence, where we showed that HIF-2a was expressed late in the sequence and was seen only in dysplasia and adenocarcinoma (Griffiths et al, 2007a). Recently, the overexpression of HIF-2a in rat gliomas was shown to have counteracting properties, in which angiogenesis was induced but reduced growth was also found due to increased tumour-cell apoptosis (Acker et al, 2005). Hypoxiainducible factor-2a expression has also been suggested to be critical in the carcinogenesis of renal cortical tumours (Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…In addition one should stress that the therapeutic use of angiogenesis inhibitors, including VEGF and prolyl hydroxylase antagonists, is likely to TEL-ARNT interferes with cellular differentiation F Nguyen-Khac et al exhibit deleterious effects both on normal differentiation and malignant cell transformation (Acker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Based on published data, the role of HIF-2α in glioblastoma formation and aggressiveness is not fully clear, as HIF-2α has been attributed a tumor-suppressor role (Acker et al 2005), as well as being a marker for poor prognosis ). Overexpression of HIF-2α protein in rat glioblastomas suppressed tumor growth despite overall enhanced vascularization.…”
Section: Non-small Cell Lung Carcinoma Hif Protein Expression Is Virmentioning
confidence: 99%
“…Overexpression of HIF-2α protein in rat glioblastomas suppressed tumor growth despite overall enhanced vascularization. This was in part explained by increased tumor cell apoptosis, and knockdown of HIF-2α in hypoxic human glioblastoma cells reduced the apoptotic rate of these cells (Acker et al 2005). Recent work on GBM has focused highly on the small fraction of tumor cells with stem cell characteristics that are thought to initiate and maintain tumor growth (Hemmati et al 2003;Singh et al 2003;Galli et al 2004;Singh et al 2004).…”
Section: Non-small Cell Lung Carcinoma Hif Protein Expression Is Virmentioning
confidence: 99%